DIDACTIC FEATURES OF TEACHING STUDENTS TO SOLVE INEQUALITIES - Bekbolganova, A.; Sarguzhiyeva, A. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
For our country to become one of the most civilized states, we need to prepare an educated generation. In this regard, one of the main tasks of the education system today is the effective use of innovative pedagogical technologies in teaching. One of these new technologies is inequality problems used in teaching and evaluating knowledge. After all, the problem system allows you to objectively evaluate students 'knowledge, check their level of training for compliance with the requirements and identify topics that caused difficulties. The process of organizing students' educational activities through inequality problems in teaching mathematics requires that each high school and college graduate be more purposeful, methodologically, and methodically justified to optimally adapt to modern industrial and social processes. In this regard, there is a contradiction between the need to train an educated, competent, conscious generation that thinks creatively in accordance with modern society and the lack of detailed study of the methodological foundations of organizing students' educational activities through testing in teaching mathematics. The identified contradiction caused the problem of our research to justify the methodology for organizing students' educational activities through testing in the process of teaching mathematics.
Keywords: inequalities; logical thinking; mathematical tasks; non- standard problems; stages of solving inequalities